Penegakan Hukum Pidana Terhadap Korporasi Pelaku Tindak Pidana Pembuangan Limbah Industri Yang Mengakibatkan Pencemaran Lingkungan Hidup Di Indonesia - Wan Fathiriansyah; Dudik Djaja Sidarta; Moh Taufik; Hartoyo Hartoyo (Journal of Innovation Research and Knowledge, 2026)
This study aims to analyze the legal framework governing corporate criminal liability and the mechanisms of criminal law enforcement against corporations responsible for industrial waste disposal that causes environmental pollution in Indonesia. A healthy environment is a constitutional right of every citizen as stipulated in Article 28H paragraph (1) of the 1945 Constitution of the Republic of Indonesia. However, the rapid development of the industrial sector is often accompanied by illegal waste disposal practices that result in significant ecological, social, and economic losses. This study employs a normative juridical method using a statutory approach and a conceptual approach. The findings indicate that the legal framework governing corporate criminal liability in Indonesia has a comprehensive normative basis through Law Number 32 of 2009 concerning Environmental Protection and Management, as amended by Law Number 6 of 2023, and supported by Supreme Court Regulation Number 13 of 2016. Normatively, corporations are recognized as subjects of criminal law that may be held criminally liable and subjected to sanctions in the form of fines and additional penalties aimed at restoring environmental functions. Nevertheless, the implementation of criminal law enforcement against corporations continues to face serious obstacles, including the complexity of proving corporate fault, the limited capacity of law enforcement officials in establishing scientific evidence, and the tendency of law enforcement authorities to prioritize prosecution of individual corporate managers rather than the corporate legal entity itself. In conclusion, effective law enforcement requires optimization through strengthening law enforcement capacity, improving inter-agency coordination, and consistently imposing sanctions on corporations to create a deterrent effect and ensure environmental sustainability in Indonesia.